The positive repercussions of the role of tourism in achieving economic and social development in Iraq - Al-Shamri, Muslim Ali (Al-Adab Journal, 2022)
It is difficult to study the tourism activity of any region without studying the natural and human components, which in turn constitute a prerequisite for establishing tourism activity and investing tourism in any area in the natural environment that was and still is one of the most important elements of tourist attractions. It plays an important role in economic and social development, but tourism has a direct impact on the environment, which is represented in the increase in the proportion of waste, especially in rural, natural and religious areas. Tourist countries have varied landmarks and tourist.It is difficult to study the tourism activity of any region without studying the natural and human components, which in turn constitute a prerequisite for establishing tourism activity and investing tourism in any area in the natural environment that was and still is one of the most important elements of tourist attractions. It plays an important role in economic and social development, but tourism has a direct impact on the environment, which is represented in the increase in the proportion of waste.